Prevention of Self-excited Vibrations in End-milling by Actively Tuning Fixture Stiffness using Fixed-fixed Beams Under Axial Load - Moore, Paul M.; Wiens, Gloria J. (8th International Conference on MicroManufacturing (ICOMM 2013), 2013)
In this paper, the development of a novel workpiece holder for micro- and meso-scale applications is discussed. Through the use of applied tensile axial force on fixed-fixed support beams, the stiffness and clamping force of the fixture can be actively tuned. Additionally, by applying varying stiffness values to two or more fixture elements working in tandem, the position of the workpiece can be manipulated. By tuning the stiffness, it was shown that the stable cutting region of end-milling operations can be effectively increased to allow for greater material removal. Other improvements in cutting operations can be achieved by using the part manipulation capability of the fixtures to make corrections in the position of the part during machining and by using the force tuning capability to reduce part deformation due to over-clamping.
Keywords: end-mill; stiffness tuning; vibrations; fixed-fixed beams; micro-scale machining; Meso-scale machining; stability